MBN 2016 Aesthetic Breast Meeting BIA-ALCL Consensus Conference Report. Issue 1 (January 2018) - Nava, Maurizio Bruno; Adams, William P.; Botti, Giovanni; Campanale, Antonella; Catanuto, Giuseppe; Clemens, Mark W.; Del Vecchio, Daniel A.; De Vita, Roy; Di Napoli, Arianna; Hall-Findlay, Elisabeth; Hammond, Dennis; Heden, Per; et al.
Abstract : Summary: Breast implant–associated anaplastic large cell lymphoma (BIA-ALCL) is an uncommon neoplasia occurring in women with either cosmetic or reconstructive breast implants. The actual knowledge about BIA-ALCL deriving from the literature presents several limits, and it remains difficult to make inferences about BIA-ALCL epidemiology, cause, and pathogenesis. This is the reason why the authors decided to organize an evidence-based consensus conference during the Maurizio Bruno Nava (MBN 2016) Aesthetic Breast Meeting held in Milan in December of 2016. Twenty key opinion leaders in the field of plastic surgery from all over the world have been invited to express and discuss their opinion about some key questions on BIA-ALCL, trying to reach a consensus about BIA-ALCL cause, pathogenesis, diagnosis, and treatment in light of the actual best evidence.